Influence of Pretreatments on Sustainability of Bioethanol Production from Napier Grass - Marthosa, Sutida; Youravong, Wirote; Anancharoenwong, Ekasit (International Journal of Integrated Engineering, 2020)
The influences of pretreatments and acid hydrolysis conditions in bioethanol production from Napier grass were investigated. The alkaline and acid pretreatments removed 6.63 % and 5.71 %  of lignin more than the untreated grass.  The recommended acid concentration in hydrolysis was 35% sulphuric acid for duration of 20 to 40 min. Fermentation of samples from acid and alkaline pretreatments for 48 h produced the highest ethanol concentration of 13 %v/v. However, when the sustainability was taken into account, these chemical pretreatments had higher cost and released more chemical to environments in comparison to steam pretreatments which produced slightly lower ethanol of 11 %v/v.